2014
DOI: 10.1177/1059712314527005
|View full text |Cite
|
Sign up to set email alerts
|

Outcome probability modulates anticipatory behavior to signals that are equally reliable

Abstract: A stimulus is a reliable signal of an outcome when the probability that the outcome occurs in its presence is different from in its absence. Reliable signals of important outcomes are responsible for triggering critical anticipatory or preparatory behavior, which is any form of behavior that prepares the organism to receive a biologically significant event. Previous research has shown that humans and other animals prepare more for outcomes that occur in the presence of highly reliable (i.e., highly contingent)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…In the case of perceptual generalisation, people are assumed to make a judgment about the similarity between GS and CS and to infer from that similarity how likely it is that the GS will be followed by the same outcome as the CS. The rule "the more stimuli look alike, the higher the chance that they will have the same outcome" can explain the typical shape of the perceptual generalisation gradient, because it has been demonstrated that subjects show stronger responding when they believe occurrence of a US to be more likely (Matute, Steegen, & Vadillo, 2014).…”
mentioning
confidence: 98%
“…In the case of perceptual generalisation, people are assumed to make a judgment about the similarity between GS and CS and to infer from that similarity how likely it is that the GS will be followed by the same outcome as the CS. The rule "the more stimuli look alike, the higher the chance that they will have the same outcome" can explain the typical shape of the perceptual generalisation gradient, because it has been demonstrated that subjects show stronger responding when they believe occurrence of a US to be more likely (Matute, Steegen, & Vadillo, 2014).…”
mentioning
confidence: 98%